Employment Effects of Special Economic Zones: Evidence from Thailand - Durongkaveroj, Wannaphong (Thammasat Review, 2022)
In 2015, Thailand established Special Economic Zones (SEZs) in ten border provinces across the country. However, despite a generous fiscal incentive package and upgraded infrastructure, the SEZs have not attracted the intended level of investment. This paper investigates the causal impacts of the SEZ policy in Thailand on employment, using a balanced panel data set covering 77 provinces from 2012 to 2020. The results of a difference-in-difference (DID) approach show that in provinces with SEZs, employment of native workers (both formal and informal) declines by 7 percent compared to provinces with no SEZs. This negative impact is largely due to a significant decrease in informal employment. There was no significant change in the number of migrant workers in treated provinces compared to those without SEZs. The findings also confirm the validity of the parallel-trends assumption and show no evidence of an anticipatory treatment effect prior to the implementation of the SEZ policy. These findings suggest that the SEZ policy needs to be revised to place more emphasis on employment generation and promoting inclusive growth through subregional development.